(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Modern European countries are actively developing an effective ecosystem of support and professional integration of people with disabilities. In particular, employers receive tax benefits and state incentives for employing specialists with disabilities. In this context, inclusive educational institutions and traditional universities must provide high-quality training for all students to compete in the labour market successfully. Developing soft skills in future engineers, particularly software engineers, is essential. Recent surveys among employers have confirmed their interest in specialists with developed soft skills, including effective communication in at least one, preferably two, foreign languages. One of the effective methods of teaching a foreign language for a professional purpose is using WebQuests. Our study analysed their impact on the educational process with the third-year bachelor students majoring in “Computer Sciences” in an inclusive environment. The research methodology combined quantitative (surveys using the Likert scale) and qualitative (teacher comments) approaches, which allowed us to obtain a comprehensive assessment of the effectiveness of web quests. A thematic Web quest, “Creating IT startup,” was developed, implemented and adapted for students with special needs (subtitled videos, audio versions of materials, accessible interface). The study results showed that students remembered professional vocabulary better and communicated more effectively in a foreign language in a professional environment. Teachers noted increased students’ involvement in ESP learning and their activity during classes. Respondents confirmed that WebQuests contributed to developing self-study skills essential for training future software engineers. The results proved the feasibility of using WebQuests to teach ESP, especially in inclusive education.